Investigation of four self-report instruments (FABT, TSK-HC, Back-PAQ, HC-PAIRS) to measure healthcare practitioners' attitudes and beliefs toward low back pain: Reliability, convergent validity and survey of New Zealand osteopaths and manipulative physiotherapists. (December 2017) - Moran, Robert W.; Rushworth, Wendy M.; Mason, Jesse
Abstract: Background: Healthcare practitioner beliefs influence advice and management provided to patients with back pain. Several instruments measuring practitioner beliefs have been developed but psychometric properties for some have not been investigated. Aims: To investigate internal consistency, test-retest reliability and convergent validity of the Fear Avoidance Beliefs Tool (FABT), the Tampa Scale of Kinesiophobia for Health Care Providers (TSK-HC), the Back Pain Attitudes Questionnaire (Back-PAQ), and the Health Care Pain and Impairment Relationship Scale (HC-PAIRS). A secondary aim was to explore beliefs of New Zealand osteopaths and physiotherapists regarding low back pain. Method: FABT, TSK-HC, Back-PAQ, and HC-PAIRS were administered twice, 14 days apart. Results: Data from 91 osteopaths and 35 physiotherapists were analysed. The FABT, TSK-HC and Back-PAQ each demonstrated excellent internal consistency, (Cronbach's α = 0.92, 0.91, and 0.91 respectively), and excellent test-retest reliability (lower limit of 95% CI for intraclass correlation coefficient >0.75). Correlations between instruments (Pearson's r = 0.51 to 0.77, p < 0.001) demonstrated good convergent validity. There was a medium to large effect (Cohen's d > 0.47) for mean differences in scores, for all instruments, between professions. Conclusions: This study found excellent internal consistency, test-retest reliability and good convergent validity for the FABT, TSK-HC, and Back-PAQ. Previously reported internal consistency, test-retest and convergent validity of the HC-PAIRS were confirmed, and test-retest reliability was excellent. There were significant scoring differences on each instrument between professions, and while both groups demonstrated fear avoidant beliefs, physiotherapist respondent scores indicated that as a group, they held fewer fear-avoidant beliefs than osteopath respondents. Highlights: Cronbach's α and test-retest reliability for FABT, TSK-HC, and Back-PAQ scores were excellent. Correlations between FABT, TSK-HC, Back-PAQ, and HC-PAIRS indicate good convergent validity. Differences in scores were observed between osteopath and physiotherapist respondents.